Obesity and Its Risk on Breast Cancer among Women: A Meta-Analysis - Ruth Apriyanti; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Breast cancer is the most common type of cancer experienced by women which can cause the most deaths in both developed and developing countries. The risk of breast cancer severity in women with BMI obesity category increased up to 30% compared with women who had normal weight. This study aims to analyze the effect of obesity on breast cancer mortality in women, with a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: breast cancer women. Intervention: obesity. Comparison: not obese. Outcome: mortality. The articles used in this study were obtained from four databases, namely Google Scholar, Pubmed, Science Direct and Springerlink. Keywords to search for articles “Obesity” OR “Obese Overweight” AND “Mortality” OR “Death” AND “Women with Breast Cancer” OR “Breast Cancer” OR “Breast Cancer Mortality” AND “Adjusted Hazard Ratio”. The included articles are full-text English with an observational cohort study design from 2012 to 2021 and report on the aOR in multivariate analyses. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 12 observational cohort studies from the United States, Denmark, Netherlands, UK, Spain, Malaysia and China were selected for systematic review and meta-analysis. The data collected showed that obesity increased the mortality risk of breast cancer women and was statistically significant (aOR = 1.23; 95% CI = 1.00 to 1.52; p = 0.050). Conclusion: Obesity increases the risk of mortality in breast cancer women. Keywords: obesity, breast cancer women, meta-analysis Correspondence: Ruth Apriyanti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ruthyanti94.ras@gmail.com. Mobile: +6281375232120.